PROBLEMS ASSOCIATED WITH THE IMPLEMENTATION OF DIGITAL TECHNOLOGY IN UZBEKISTAN'S HIGHER EDUCATION INSTITUTIONS - O'rozaliyev, Elyor (Журнал математики и информатики, 2023)
Because of the incorporation of digital technologies in recent years, the worldwide landscape of higher education has experienced substantial modifications. Uzbekistan acknowledges the significance of aligning with this global trend and is aggressively seeking digital technology deployment in its higher education institutions. The purpose of this thesis is to evaluate the existing status of digital technology integration in Uzbekistan's higher education system and to forecast probable future trends.